The Services provided to the families of people with quadriplegia in Saudi Arabia - Alsaloom, Waleed Abdullah (Journal of Humanities & Social Sciences, 2021)
The study aimed to know the most important needs of the families of quadriplegics in the Kingdom of Saudi Arabia from their point of view and from the point of view of social workers. To achieve the goal of the study, the researcher used the descriptive survey method, and the study sample consisted of (120) of the families of quadriplegia, in addition to (70) Social worker. The researcher used the questionnaire as a tool for the study. The results of the study showed the approval of the families of quadriplegic patients on the services provided to the families of quadriplegic patients with an average of (4.17), and that the most important services are as follows:: helping the family to accept appropriate treatment methods, alerting the parents to the necessity of meeting the patient's medical, psychological and social needs, and convincing the patient's family that the patient should not be isolated from his community, Explain all positive methods that help the patient's family in dealing with him, facilitate the patient's medical services in the medical institution and that ensure more patient comfort, and encourage the patient's family to accept the patient's condition, help the patient's family move beyond the stage of searching for methods that led to the disease, support specialist Social network of relationships between the family and the patient, educating the family about the behavioral prohibitions that should be avoided in front of the patient. The results of the study also showed the approval of the social workers on the services provided to the families of quadriplegic patients with an average of (4.33), and that the most important of these services are the following: providing a quadriplegic patient to the family and informing them in an appropriate manner, and relieving the patient’s family during the patient’s entry to receive treatment, helping the family to accept appropriate methods and methods of treatment, Helping the patient’s family in understanding the social, economic and emotional factors and their relationship to the patient’s condition, with an arithmetic average, providing assistance in the stage of overcoming the trauma in which feelings are mixed, educating the family about behavioral prohibitions that should be avoided in front of the patient, and helping the patient’s family in Passing the stage of searching for methods that led to the disease.
Keywords: services; families; quadriplegics